Edward Gibbon - Womersley, D (Voltaire Foundation, 2017)
In the summer of 1994, on the occasion of the bicentenary of Gibbon’s death, a group of scholars gathered in Oxford to commemorate and explore his achievement, producing this volume of essays. Eighteen years earlier, in 1976, there were similar gatherings for the bicentenary of the publication of the first volume of The Decline and fall, likewise producing published collections of essays. Comparing the present volume with its predecessors, how has scholarship devoted to Gibbon changed in the intervening years? The dominant theme of Gibbon studies during this recent period has been ‘disaggregation’, and this can be understood in two senses. Firstly, there has been textual disaggregation. Works which earlier scholars were content to treat as ‘un ensemble’ are today scrupulously delaminated: manuscripts are compared, different editions collated, separate instalments discriminated, successive drafts juxtaposed. It seems safe to say that no modern study of Gibbon could gain a hearing unless its author was evidently a master of the relevant textual bibliography. The result of this renewed interest in bibliography has been a much sharper awareness of the complexity of Gibbon’s writings as literary artefacts. Secondly, disaggregation has also occurred in the contexts, both English and European, within which Gibbon’s work demand to be read. The Enlightenment itself is now apprehended as a congeries of movements and events that attracted men of divergent aims and beliefs. In this freshly complicated setting, Gibbon’s life and work emerge as key points, through which swirled many of the most important intellectual currents of the day. The essays collected in this volume exemplify and extend these trends in Gibbon scholarship. Preface Acknowledgements List of abbreviations I Gibbon and Europe II The Decline and fall: milieu, substance and reception III After The Decline and fall Notes on contributors Index